Charles IV. Portrait of a Medieval Ruler - Václav, Žůrek (Karolinum, 2025)
Charles IV, King of Bohemia and Holy Roman Emperor, has been called "one of the most learned and diplomatically skillful sovereigns" of the fourteenth century. Having moved the seat of the Holy Roman Empire to Prague and founding the first university in Central Europe, Charles IV is a towering figure in Czech history and a crucial character in the story of medieval Europe. Recent research, especially in art history, has tended to present Charles IV in a purely positive, unblemished light: viewing him and his imperial court as the engine behind a flourishing of culture in the region. This book views Charles IV through a more critical lens, examining the careful construction that went into the way he presented himself, winning over people of the time and even today, as well as the most characteristic manifestations of Charles' execution of royal power. The first part of the book offers a chronological description of Charles' life within the broader context of the times and the House of Luxembourg. The second part provides a close look into Charles IV's style of rule while focusing on phenomena that reveal his personal conception of power and how it was wielded.
Keywords: Dějiny